2005
DOI: 10.1149/1.1945567
|View full text |Cite
|
Sign up to set email alerts
|

1-Alkyl-3-methylimidazolium Bis(perfluoroalkylsulfonyl)imide Water-Immiscible Ionic Liquids

Abstract: This study presents the electrochemical properties of room-temperature ionic liquids ͑RTILs͒ at a variety of liquid-liquid interfaces. The RTILs used here consist of 1-alkyl-3-methylimidazolium ͑C n mim, n = 6, 8, 10, 12͒ cations with bis͑perfluoromethyl-sulfonyl͒imide ͑BMSI͒ and bis͑perfluoroethylsulfonyl͒imide ͑BETI͒ anions. Ion transfer across the polarizable 1,2-dichloroethane/ water and the neat RTIL/water interfaces were examined. The ion-transfer experiments suggested that the RTILs made with C n mim an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(72 citation statements)
references
References 54 publications
0
70
2
Order By: Relevance
“…The sensitivity is often attributed to enhanced ion conductivity and/or concentration 32,33 . On the other hand, hydrophobic ionic liquids show minimal sensitivity to humidity, with the response decreasing with increasing hydrophobicity 34,35 . We observe the same trend in the conductance and capacitance of our liquid-state heterojunction devices (Fig.…”
Section: Article Nature Communications | Doi: 101038/ncomms6032mentioning
confidence: 99%
“…The sensitivity is often attributed to enhanced ion conductivity and/or concentration 32,33 . On the other hand, hydrophobic ionic liquids show minimal sensitivity to humidity, with the response decreasing with increasing hydrophobicity 34,35 . We observe the same trend in the conductance and capacitance of our liquid-state heterojunction devices (Fig.…”
Section: Article Nature Communications | Doi: 101038/ncomms6032mentioning
confidence: 99%
“…This is consistent with the fact that alkyl groups are electron-donating in nature and hence would tend to stabilize a cation against reduction. Fitchett et al [12] • The initial effect of alkylation on the EA is greater than subsequent alkylation. This may be explained by the fact that the initial alkylation typically takes place at hydrogens connected to the aromatic ring structure (in the case of imidazolium or pyridinium based ions) or the atom of formal positive charge (e.g.…”
Section: Effect Of Alkylation On Eas Of Cationsmentioning
confidence: 99%
“…In the case of ILs, this is further compounded by their sensitivity to water, air and other impurities. [12,13,14] For example, Randstrom et al [13] have recently shown that while the innate cathodic stability of pure and dry ILs are generally set by the reduction potential of the cation, anion reduction [15] may occur at a higher potential than cation reduction in the presence of water and oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…The main impurities in ILs are water and halide ions. Electrochemically speaking, water impurities have been shown to decrease the viscosity (Widegren et al, 2005;Zhang et al, 2006), increase the conductivity (Fitchett et al, 2005) and shrink the electrochemical window significantly (Schröder et al, 2000;Fitchett et al, 2005). Although water is by far the major impurity affecting the ILs, O2 from air is also easily dissolved in the ILs and often accompanies water; since this molecule is electroactive, its removal is required before any electrochemical measurement (Ohno, 2005).…”
Section: Destruction Of Thiophene Using Potassium Superoxidementioning
confidence: 99%